Perubahan Bunyi Fonologi dalam Gangguan Psikogenik Tuturan Manja Pada Remaja Dewasa - Indriyani, Indriyani; Kalamsyah, Isnayni; Tisnasari, Sundawati (Innovative: Journal Of Social Science Research, 2025)
Language speakers are not only on the side of direct communication; they may also be seen as individuals with established psychological. This psycholinguistic study examines the phenomenon of psychogenic language disorder in the form of childlike speech behavior among young adults, focusing on a subject referred to as VA (20 years old) who exhibits such speech patterns with her partner. The aim of this research is to describe the phonological alterations that occur and to identify the psychological factors underlying this childlike speech behavior. This study employs a qualitative descriptive method with a case study approach, using observation and interviews as data collection techniques. The findings reveal that the subject's childlike speech behavior involves various phonological changes, such as dissimilation, anaptyxis, metathesis, and zeroization. This phenomenon is not caused by any physical disorder, but rather by a psychological drive to seek attention and affection. These findings highlight the significant role of psychological aspects in language production and underscore the importance of considering psychogenic factors in psycholinguistic studies, particularly in understanding mild language disorders of psychological origin.